Identifying the meaning of song titled “imagination” through experiential function: A case on systemic functional linguistics - Tampubolon, Nandito; Turnip, Gresy; Nurmika Turnip, Anggreni; Sinaga, Yanti Kristina; Batubara, Junita; Van Thao, Nguyen (Institute of Education and Social Research, 2024)
This research aims to determine the type of transitivity process from the of song Imagination and find the dominant type of process used in the song Imagination. This research was conducted using qualitative research methods and using data analysis. The data used as a source are song lyrics that use a paler lyrical instrument. Data collection was carried out by reading and understanding the lyrics to analyzing each clause and type of transitivity system in the song. In the analysis of the song Imagination found 67 clauses with the type of transitivity system count analyzed, namely 61 processes with the highest usage order, namely Mental, Attributive relational, Material, Verbal, Possession relational, Identifying relational and behavioral. 99 participants with the highest usage order, namely Senser & Carrier, Phenomenon, Attribute, Actor, Sayer & Target, Verbiage & Goal, Possessor & Possessed, Value & Token. And 29 Circumstances with the order Extent temporal, Location Spatial & Accompaniment, Manner, Contingency and Location temporal & Matter. Thus, it can be concluded that the dominant type of transitivity system used in the song Imagination, namely Mental Processes with the proportion (39%) of Participant Senser and Carrier with the proportion of each (17%) and Circumstances Extent (Temporal) with the proportion (21%).